Eksperimentasi Arah Dengar Penyandang Disabilitas Sensorik Netra terhadap Munculnya Audio: Experimentation of Hearing Direction of Blind Sensory Disability to the Emergence of Audio - Sumpena, Della Dwinanti; Surya, Ibrahim Adi; Widjajanto, Kenmada; Akbar, Muhammad (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
In general, film media is a common entertainment media in society, which can actually be enjoyed in terms of visual and audio. However, in the experience of watching a film, there are special needs for people with sensory disabilities who are blind who have limited vision. Media transfer is something that will be done in this research process, so that the essence of the film itself can still be enjoyed by people with sensory disabilities. Through a qualitative research method, by taking an observational approach to people with sensory disabilities who are blind, the transfer of film media becomes a means of conveying communication from film media which generally consists of video and audio to audio media. Supporting the Sustainable Development Goals (SDG's), one of the goals of which is to prioritize inclusive and equal quality education, especially in this case for people with sensory disabilities who are blind. This experimental process was carried out as initial research in the development of ways and techniques for telling audio media so that it can be well received by people with sensory disabilities who are blind, informatively and based on the messages conveyed in it. The conclusion of this study resulted in an analysis of the experience of identifying the direction of hearing for people with visual disabilities. Seeing the form of audio film needs to be formed by paying attention to the details of the needs of each person with visual disabilities, then this process becomes something that needs to be tested first. So from the samples found there are several identifications that need to be tested further, and this process becomes one thing that will be tested again to get an analysis that is more in accordance with the needs of people with visual disabilities.